2013
DOI: 10.1021/om400515g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Redox-Active Mononuclear Fe(κ2-dppe)(η5-C5Me5)-Terminated π-Conjugated Wires

Abstract: International audienceSeveral new redox-active Fe(κ2-dppe)(η5-C5Me5) arylacetylide complexes featuring pendant ethynyl (Fe(κ2-dppe)(η5-C5Me5)[{C≡C(1,4-C6H4)}nC≡CH] (1b-d; n = 1-3), Fe(κ2-dppe)(η5-C5Me5)[C≡C(1,3-C6H4)C≡CH] (2)) or ethenyl (Fe(κ2-dppe)(η5-C5Me5)[C≡C(1,4-C6H4)CH═CH2] (3)) groups have been synthesized and characterized under their Fe(II) and Fe(III) states. In contrast to the known ethynyl Fe(III) complex [Fe(κ2-dppe)(η5-C5Me5)(C≡CH)][PF6] (1a[PF6]), most of the new Fe(III) derivatives turned out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
33
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 87 publications
4
33
1
1
Order By: Relevance
“…26,27 Comparison of spectra of organoiron-modified porous Si(100) surfaces with that of hydrogen-terminated porous Si(100) evidenced ν CCFe vibration bands characteristic of the immobilized organometallic center at 2054, 2048, and 2046 cm −1 for Si-1b−d, respectively (Figure 3a), which are consistent with the values and trends observed for the complexes (Figure 3b). 18 In the ν CC stretching vibration region (i.e., between 1600 and 1400 cm −1 ), the presence of a band at 1589 ± 2 cm −1 in the spectrum of Si-1b−d can be ascribed to the 1,4-phenylene spacer, while the CHCH unit bound to the silicon surface at 1570 cm −1 are not always plainly detected but show up as a shoulder to the previous peaks. 28 This is somewhat comparable to the value near 1620 cm −1 attributed to the ν CHCH 2 mode for 3.…”
Section: ■ Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…26,27 Comparison of spectra of organoiron-modified porous Si(100) surfaces with that of hydrogen-terminated porous Si(100) evidenced ν CCFe vibration bands characteristic of the immobilized organometallic center at 2054, 2048, and 2046 cm −1 for Si-1b−d, respectively (Figure 3a), which are consistent with the values and trends observed for the complexes (Figure 3b). 18 In the ν CC stretching vibration region (i.e., between 1600 and 1400 cm −1 ), the presence of a band at 1589 ± 2 cm −1 in the spectrum of Si-1b−d can be ascribed to the 1,4-phenylene spacer, while the CHCH unit bound to the silicon surface at 1570 cm −1 are not always plainly detected but show up as a shoulder to the previous peaks. 28 This is somewhat comparable to the value near 1620 cm −1 attributed to the ν CHCH 2 mode for 3.…”
Section: ■ Introductionmentioning
confidence: 91%
“…Toward this aim, using a photochemical grafting protocol previously communicated, 17 we have now isolated the corresponding monolayers on Si−H (Chart 1), starting from a series of mononuclear Fe(κ 2 -dppe)(η 5 -C 5 Me 5 ){[CC(1,4-C 6 H 4 )] n CCH} (1a−d; n = 0−3), Fe(κ 2 -dppe)(η 5 -C 5 Me 5 )[CC(1,3-C 6 H 4 )CCH] (2), and Fe(κ 2 -dppe)(η 5 -C 5 Me 5 )[CC(1,4-C 6 H 4 )CHCH 2 ] (3) complexes previously synthesized. 18 From such functional interfaces, electrochemical studies on 1a−d-modified Si−H surfaces (Si-1a−d) should reveal the incidence of the phenylethynyl spacer extension on the interfacial electrontransfer characteristics, while comparison among Si-1b, Si-2, and Si-3 should bring complementary information on the topological and structural features which are determining for this property with this kind of unsaturated spacer.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, computationally oriented chemists can provide crucial information on these molecules, especially thanks to the very recent developments in this area [13][14][15][16]. Furthermore, Density Functional Theory (DFT) and its TimeDependent extension (TD-DFT) are increasingly used to get electronic and vibrational information from small-to large-size systems thanks to the strong improvements in hardware and software [17][18][19][20][21][22][23]. Among all its possibilities, the DFT approach can be used for the prediction or confirmation of compounds [21,24,25] and the explanation of the luminescent and spectroscopic properties of multi-scale systems [13, [26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] Moreover, Density Functional Theory (DFT) and its time dependent extension (TD-DFT) are now routinely used to get both electronic and vibrational information from small organic to large-size organometallic and transition metal complexes systems. [10,[24][25][26][27][28][29][30] Indeed, DFT calculations are now accurate enough to predict or confirm the stability or existence of compounds, and they can also explain the luminescent and/or spectroscopic properties of complex systems. [31][32][33][34][35][36][37][38][39][40] In the field of spectroscopy calculations, Vlcek Jr. and Zális among other authors, have shown how DFT and TD-DFT are useful tools to study d 6 metal complexes.…”
Section: Introductionmentioning
confidence: 99%